Extracellular vesicles, exosomes and shedding vesicles in regenerative medicine – a new paradigm for tissue repair. (29th November 2017) - Bjørge, I. M.; Kim, S. Y.; Mano, J. F.; Kalionis, B.; Chrzanowski, W.
Abstract : Extracellular vesicles are highly specialized messengers that deliver vital biological signals including ribonucleic acids – key modulators in tissue regeneration. Abstract : Tissue regeneration by stem cells is driven by the paracrine activity of shedding vesicles and exosomes, which deliver specific cargoes to the recipient cells. Proteins, RNA, cytokines and subsequent gene expression, orchestrate the regeneration process by improving the microenvironment to promote cell survival, controlling inflammation, repairing injury and enhancing the healing process. The action of microRNA is widely accepted as an essential driver of the regenerative process through its impact on multiple downstream biological pathways, and its ability to regulate the host immune response. Here, we present an overview of the recent potential uses of exosomes for regenerative medicine and tissue engineering. We also highlight the differences in composition between shedding vesicles and exosomes that depend on the various types of stem cells from which they are derived. The conditions that affect the production of exosomes in different cell types are deliberated. This review also presents the current status of candidate exosomal microRNAs for potential therapeutic use in regenerative medicine, and in applications involving widely studied organs and tissues such as heart, lung, cartilage and bone.